2011
DOI: 10.1080/17470218.2011.559586
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Working Memory Capacity in Multiple-Cue Probability Learning

Abstract: Multiple-cue probability learning (MCPL) involves learning to predict a criterion when outcome feedback is provided for multiple cues. A great deal of research suggests that working memory capacity (WMC) is involved in a wide range of tasks that draw on higher level cognitive processes. In three experiments, we examined the role of WMC in MCPL by introducing measures of working memory capacity, as well as other task manipulations. While individual differences in WMC positively predicted performance in some kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 73 publications
1
24
1
Order By: Relevance
“…Each consecutive period shifted by one‐year intervals (i.e., 22–31, 23–32, and so on) until age 68–77 years. This approach has been used to capture subtle trends in data that can be missed by a single regression model . The smaller the period (e.g., 20–29 vs. 20–49), the smaller the overlap across consecutive periods and so the greater the detection of subtle age trends.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each consecutive period shifted by one‐year intervals (i.e., 22–31, 23–32, and so on) until age 68–77 years. This approach has been used to capture subtle trends in data that can be missed by a single regression model . The smaller the period (e.g., 20–29 vs. 20–49), the smaller the overlap across consecutive periods and so the greater the detection of subtle age trends.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been used to capture subtle trends in data that can be missed by a single regression model. (44) The smaller the period (e.g., 20-29 vs. , the smaller the overlap across consecutive periods and so the greater the detection of subtle age trends. We struck a balance between the size of the period and its sample size, ensuring that the smallest sample contained no fewer than 34 participants (min = 34, max = 95, M = 54.63; SD = 17.20).…”
Section: Analytical Approachmentioning
confidence: 99%
“…The latter finding may be due to a greater difficulty for participants to learn a negative contingency between box outcome and overall winner (cf. Betsch et al, 2016; see also Busemeyer et al, 1997; Rolison et al, 2011, for a description of similar results in the prediction of continuous criterion). A subsequent analysis was conducted to examine this possibility.…”
Section: Resultsmentioning
confidence: 72%
“…Taken together, these illustrative experiments provide little evidence that unconscious processes influence multicue judgment. The dominant pattern across the experiments in both the Evans et al (2003) and Rolison et al (2011) studies was of significant positive correlations between measures of performance and explicit knowledge of cue relevance/usage. In those instances where such correlations were absent, procedural artifacts (e.g., timing of awareness assessment) may have been responsible.…”
Section: Examining Insight In Novice Judgesmentioning
confidence: 95%
“…In a recent study Rolison et al (2011) used similar methods to investigate the role of working memory capacity (WMC) in multicue judgment. They found that WMC correlated with performance when tasks involved negative predictors, but not when all relevant cues were positive predictors.…”
Section: Examining Insight In Novice Judgesmentioning
confidence: 99%